A study of the potentials of traditional natural resources management for biodiversity conservation - Jagdish Bihari Gangadhar; Manmohan Khan; Akshay Ram Premji (African Journal of Environmental Economics and Management, 2018)
Social taboos exist in invariably all cultures throughout the world, and represent a class of informal institutions, where traditional, religiously governed norms or taboo system define the human behaviour. These taboos remain the prime factor guiding their conduct towards the exploitation of the natural resources. However, the singular role played by these informal systems of taboo in conservation of biodiversity has not been given its due importance. The present paper attempts to render forth the salient aspect of conservation borne out of the taboo system in practice surrounding the sacred natural sites, principally the sacred forests, in the state of Uttarakhand, central Himalaya. The study brings forth the fact that although the potential of traditional natural resources management for biodiversity conservation vis a vis the institution of taboo within the state remains enormous, the sustainability of these practices however is seriously threatened. In fact, the dilution of the traditional beliefs and associated taboos, principally borne out of the western type education, along with social and economic factors, underpinning traditional natural resources management practices were found to be the greatest threat to the sustainability of these practices. There is thus an urgent need to investigate local perceptions of forest space and landscape, biodiversity conservation and traditional beliefs, and their significance for natural resources management, towards understanding the changing values of local people in relation to traditional protected areas, such as sacred forests.